Development Issues and Potential Safeguards: A Study on Bangladesh Stock Market - Hossain , Md. Toufique (Global Disclosure of Economics and Business, 2016)
The capital market is a very prankish place that holds two types of risk. One is the risk at the efficiency level of the market that refers to the structural weakness. And the other one is the man-made danger that indicates the stakeholders’ irrational behaviors some examples of which are manipulation, gambling, speculation, rumor and so on. Out of the two, the structural weakness is a sensitive issue of the market, and it can be abated at a great extend when the market is properly structured. Here, the author has mentioned five shields which are termed as the “Financial Safeguards” symbolically. Those are adapting Corporate Governance, introducing Financial Reporting Act, making stock market tribunal, exploring product diversification and enhancing the investors’ knowledge. The complete implementation of these safeguards is absent in Bangladeshi market though they leave a little impact. This article examines those points and how they can be effective rooting the existing problems out from the market. JEL Classification code: D53, G1, G3